Microstructural analysis of co-sintered PSLZT-NZFO layered magnetoelectric composite. (18th August 2017) - Premkumar, S.; Varadharajan, E.; Rath, Martando; Mathe, V. L.; Ramachandra Rao, M. S.
ABSTRACT: In this study we made an attempt to fabricate magnetoelectric composite of magnetostrictive NZFO layer on piezoelectric PSLZT multilayer by co-sintering them directly. Microstructural analyses of the layered composite were made to study their interface which is crucial for elastic coupling. Initially (Ni0.7 Zn0.3 )Fe2 O4 and (Sr, La) modified PZT were synthesized by solid oxide route, thick films of them were fabricated by tape casting technique with layer thickness of 100 μm and these layers were laminated together. Here Ag-Pd electrodes were screen printed on individual piezoceramic layers. These NZFO-PSLZT laminated composites were co-sintered between 950 to 1050°C for 2 h. Individual layers of NZFO and six layers of PSLZT with Ag-Pd electrode were also sintered in the same condition for comparison. Scanning electron microscopy was employed to analyze the interface of the co-sintered multilayer. Microstructures of the composite cross section revealed dense thick film with less inter diffusion. Magnetic force microscopy (MFM) was utilized to study the magnetic domains on top surface of individual NZFO layer and NZFO-PSLZT composite. Dielectric behavior of six layered PSLZT was compared with laminated NZFO-PSLZT composite. The properties of co-sintered NZFO-PSLZT composite were correlated with its microstructure.